The Bergamo underworld. Analysis of a criminal phenomenon (Rivista di Studi e Ricerche sulla criminalità organizzata, 2017)
During Seventies and Eighties, the areas of Val Seriana (the valley originated from the Serio river) and Val Cavallina (the valley originated from Cherio river), in the provence of Bergamo (Northern Italy), were crossed by a criminal phenomenon generically called “malavita bergamasca”, a particular autochthonous criminal organization. The aim of this article, developed especially through indepth interviews with former members of the organization, is trying to explore the origins of this criminal experience, its structures, cultural codes and the relations with mafia groups based in the area of Bergamo.Keywords: Bergamo, organized crime, Northern Italy criminal organization, bank robbery, imprisonmet and criminal opportunities